PERBANDINGAN PIJAT WOOLWICH DAN PIJAT OKSITOSIN TERHADAP PRODUKSI ASI IBU POSTPARTUM DI PMB X KAMPAR - Siregar, Wilda Artika Sari; Rahmi, Rifa; Mardiya, Rizka; Aifa, Wira Ekdeni (Jurnal Ilmu Kebidanan, 2024)
Breast milk is a white liquid produced by the mother's breast glands through the breastfeeding process and is one of the best foods for babies. The aim of this study was to determine the effect of Woolwich massage and oxytocin massage on breast milk production in postpartum mothers at PMB Bd. Fuchia Yulivel Asneldy, S.Tr.Keb., M.H (Kes). This type of research is Pre-Experiment research with a Two group pretest-posttest research design. The research was conducted in May-July 2024. The population in this study was all postpartum mothers at PMB Bd. Fuchia Yulivel Asneldy, S.Tr.Keb., M.H (Kes) total sample of 32 respondents with purposive sampling technique using the Wilcoxon Signed Ranks Test and the Mann Whitney Test. The results of this research showed that breast milk production before the Woolwich massage was 55.00 ml and after the Woolwich massage 365.00 ml and before the oxytocin massage 59.38 ml and after the Oxytocin massage 365.75 ml. The p-value obtained for the Woolwich Massage was 0.000425<0.05 while the p-value for the Oxytocin Massage was 0.000413<0.05 while the comparison for the Woolwich massage was 15.41 ml and the comparison for the oxytocin massage was 17.59 ml with a difference of 2.18 ml then Ho is accepted and Ha is rejected, meaning there is a difference in Woolwich Massage and Oxytocin Massage on breast milk production in postpartum mothers in PMB Bd. Fuchia Yulivel Asneldy, S.Tr.Keb., M.H (Kes) Kualu Village, Tambang District, Kampar Regency.